Goal programming: application in the management of the Miombo woodland in Mozambique - Nhantumbo, I.; Dent, J.B.; Kowero, G.S. (2001)
Community-based management of natural resources is a priority in Mozambique's policy on forestry and wildlife resources. In essence the government’s policy is to manage the natural resources in partnership with the rural communities and the private sector. This represents a change in policy in the agricultural and natural resources sectors, and has potential for significant impact in economic development. This paper demonstrates the potential for employing goal programming as a planning tool in participatory natural resource management in Mozambique. The focus is on the miombo woodlands which are the main natural forest resources in the country and which most of the local communities, the forestry and tourist industries depend on for a variety of forest products and services.